A qualitative evaluation of an NHS Weight Management Programme for obese patients in Liverpool. Issue 2 (4th March 2014) - Webb, Richard; Davies, Ian; Johnson, Brian; Abayomi, Julie
Abstract : Purpose: – The increasing prevalence of obesity in the UK has been of concern for some time. This is particularly true in Liverpool and in response the Liverpool Weight Management Programme (LWMP) was devised. It offers a service involving dietitians and other expert agencies working towards facilitating dietary and lifestyle changes in obese NHS patients in Liverpool via a 12-week education programme. This qualitative study aims to investigate patients' experiences of the LWMP. Design/methodology/approach: – Informed volunteers participated in focus groups exploring their experiences following the programme. Focus groups were audio recorded and transcribed verbatim, then analysed following a thematic approach utilising constant comparison analysis to allow a qualitative view of the LWMP to be formed. Findings: – Participants described an increase in immediate self-confidence during the LWMP, as opposed to coercion and pressure experienced elsewhere. The results also show the implementation of dietary changes by participants and favourable opinions towards both the group settings and patient-centred care. Participants also positively described the LWMP regarding the programmes social approach and aspects of programme content; however, there were issues with over-dependence on healthcare professionals. Healthcare professionals also need to recognise that long-term empowerment may still be lacking and that follow-up support and the effectiveness of some areas of programme content need to be considered to ensure patients benefit from sustainable weight management. Originality/value: – This paper addresses an identified need for qualitative research in the area of health service weight management programmes and highlights the importance of long-term support in empowering patients by exploring their lived experience of the LWMP.